Effects of Low and High FODMAP Diets on Human Gastrointestinal Microbiota Composition in Adults with Intestinal Diseases: A Systematic Review - Vandeputte, Doris (Microorganisms, 2020)
A diet high in non-digestible carbohydrates is known to promote health, in part through its effect on the gut microbiome. While substantially proven for healthy individuals, these effects are more ambiguous in subjects with intestinal diseases. At the same time, a diet low in these fermentable carbohydrates, the low FODMAP (acronym for Fermentable Oligo-, Di-, Mono-saccharides, And Polyols) diet, is gaining popularity as a treatment option for symptom relief in irritable bowel syndrome and inflammatory bowel disease. There are, however, several indications that this diet induces effects opposite to those of prebiotic supplementation, resulting in gut microbiome changes that might be detrimental. Here, we provide a systematic review of the effects of low and high FODMAP diets on human gastrointestinal microbiota composition in adults with intestinal diseases, through literature screening using the databases PubMed, Embase, and Web of Science. We summarize study findings on dietary impact in patients, including the effect on bacterial taxa and diversity. In general, similar to healthy subjects, restricting non-digestible carbohydrate intake in patients with intestinal diseases has opposite effects compared to prebiotic supplementation, causing a reduction in bifidobacteria and an increase in bacteria associated with dysbiosis. Future studies should focus on assessing whether the induced microbial changes persist over time and have adverse effects on long-term colonic health.